1960
DOI: 10.1007/bf00631384
|View full text |Cite
|
Sign up to set email alerts
|

Über die Struktur der komplexen Perkuprate

Abstract: Direct Visualization of the Haemoglobin Molecules Indirect determinations of the shape and size of the haemoglobin molecules, careers of oxygen in blood, have been made by different authors~-~). I n the present work, the mole-The electron microscopic evidence t h u s greatly corroborates the very recent works of PERIJTZ et al.S).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1961
1961
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 1 publication
2
13
0
Order By: Relevance
“…This observation is attributed to a reaction between similarly charged species. Overall, this oxidation reaction can be assigned an innersphere mechanism, which is consistent with the reported behavior of IO 4 as a ligand binding to copper(III) [19] and nickel(IV) [20], such that coordinated H 2 O is substituted by IO 4 - [8][9][10][11][12]. Also, it may be concluded that from the reported equilibrium constants of aqueous IO 4 solutions …”
Section: Kinetics Of Oxidation Of the Complexsupporting
confidence: 85%
See 1 more Smart Citation
“…This observation is attributed to a reaction between similarly charged species. Overall, this oxidation reaction can be assigned an innersphere mechanism, which is consistent with the reported behavior of IO 4 as a ligand binding to copper(III) [19] and nickel(IV) [20], such that coordinated H 2 O is substituted by IO 4 - [8][9][10][11][12]. Also, it may be concluded that from the reported equilibrium constants of aqueous IO 4 solutions …”
Section: Kinetics Of Oxidation Of the Complexsupporting
confidence: 85%
“…The value of K 3 indicates that H 3 IO 6 2is not the predominant species (IO 4 is used to represent H 4 IO 6 -) [19]. The Cr(III) will also be subject to an equilibrium in acid medium, as shown in Eq.…”
Section: Kinetics Of Oxidation Of the Complexmentioning
confidence: 99%
“…The oxidation of [Cr III (HNTA)(Hist)-(H 2 O)] -by periodate probably involves an inner-sphere mechanism. This assignment is supported by the fact that [IO 4 ] -is capable of acting as a ligand, as demonstrated by its coordination to copper(III) [29] and nickel(IV) [30], in which coordinated H 2 O is substituted by I VII [13].…”
Section: Discussionmentioning
confidence: 86%
“…From the above discussion, the following mechanism is proposed for the oxidation of [Cr III (HIDA)(Asp)(H 2 O) 2 ] + by periodate which supported by the observation that the ion is capable of acting as a ligand, as is apparent from its coordination to copper(III) [25] and nickel(IV) [26]. The oxidation of [Cr III (HIDA)(Asp)(H 2 O) 2 ] + by periodate may proceed via one or two electron transfer giving chromium(IV) or chromium(V), respectively in the rate determining step leading to chromium(VI).…”
Section: Mol Dmmentioning
confidence: 84%